Impairment of Granzyme B-Producing Regulatory B Cells Correlates with Exacerbated Rheumatoid Arthritis - Xu, Liling; Liu, Xu; Liu, Hongjiang; Zhu, Lei; Zhu, Huaqun; Zhang, Jian; Ren, Limin; Wang, Pingzhang; Hu, Fanlei; Su, Yin (Frontiers in Immunology, 2017)
Hyper-activated B cells have been demonstrated the contribution to the development of Rheumatoid arthritis (RA). While the recognition of the negative regulatory function of B cells further promoted our understanding of their pathogenic role in RA. Recently, a new population of granzyme B-producing B cells was identified, which was proved to be involved in cancer and infectious diseases. However, their characteristics and roles in RA remain to be elucidated. In the present study, we aim to further characterize whether B cells could produce granzyme B and reveal their potential role in the pathogenesis of RA. Here, we further demonstrated peripheral blood B cells from healthy individuals could produce and secrete granzyme B, which could be enhanced by IL-21 and/or anti-BCR stimulation. These cells could negatively regulate Th1 and Th17 cells partly via down-regulating TCR zeta chain and inducing T cell apoptosis, which might be termed as granzyme B-producing regulatory B cells (Breg). These granzyme B-producing Breg were significantly decreased under RA circumstance concomitant of lower levels of IL-21 receptor, with impaired regulatory functions on Th1 and Th17 cells. Moreover, the frequencies of these cells were negatively correlated with RA patient disease activity and clinical features. After effective therapy with disease remission in RA, these granzyme B-producing Breg could be recovered. Therefore, our data revealed that B cells could produce granzyme B with immunosuppressive functions, and the impairment of this Breg subset was correlated with RA pathogenesis.